From Collective Memory to Commemoration - SAITO, Hiro (Institutional Knowledge at Singapore Management University, 2010)
To have “memory” of an event, humans have to experience it themselves. Learning of an event secondhand, humans acquire knowledge, but not memory. Yet, when sociologists speak of “collective memory,” they routinely include as agents of memory those who do not have firsthand experience of a past event. This inclusion has been taken for granted ever since Maurice Halbwachs (1992) formulated his Durkheimian theory of the relationship between collective memory and commemoration in terms of group solidarity and identity: collective memory emerges when those without firsthand experience of an event identify with those who have such experience, defining both sets of actors as sharing membership in the same social group. The creation of this affect-laden, first-person orientation to a past event is at the crux of commemoration—simply put, a ritual that transforms “historical knowledge” into “collective memory” consisting of mnemonic schemas and objects that define the meaning of a past event as a locus of collective identity. According to Halbwachs’s formulation, commemoration is a vehicle of collective memory.